From luxury architecture treatise to practical manual: the Dutch editions of Scamozzi's L'ldea della Architettura Universale* (Bulletin KNOB, 1997)
The architecture treatise ‘L'ldea della Architettura Universale’ first appeared in a Dutch translation in 1640, published by Cornelis Danckerts from Amsterdam. This first edition in folio format, abundantly supplied with illustrations and text, only comprised the sixth Book of the treatise, on the subject of the orders of columns.His plan of publishing the whole treatise in a complete translation appears from the journey his son Dancker Danckerts made to Venice in 1655 to buy the original woodcuts from the heirs. However, these plans were thwarted by Symon Bosboom, stonemason by trade and as such involved in the building of the Amsterdam Town Hall, who published a simplified version of the treatise in 1657.This consisted of a short introductory text and chiefly illustrations that could easily be imitated by pupils and amateurs of architecture. In 1662 and 1664 rival editions were published by Joachem Schuym and Joost Vermaarsch respectively, both intended to explain the material of Scamozzi - in the case of Vermaarsch combined with theories of Palladio and Serlio - as simply and clearly as possible.Attempts by Danckerts to retain the market for the luxury edition by means of some cosmetic adaptations and the addition of all the original illustrations, turned out to be useless, however. Consequently, Dancker Danckerts and his successors in the family business opted for taking over the simplified editions. Until in the eighteenth century these adaptations, among which Bosboom's edition proved to have greatest commercial success, were published in a practically unchanged form.Until the middle of the nineteenth century these editions continued to be used as practical sample books for the education of artists and architects. The last editions, from 1784 onwards, introduce some innovations in the text, playing along with the new developments: the rules of architecture appear no longer to be determined from on high, but by the artist himself. This development marks the end of a successful publication history of Bosboom's treatise. The last edition appeared in 1854.